Statistiques UIS - UNESCO (2021)
L'Institut de statistique de l'UNESCO (ISU) est la source officielle et fiable de données comparables à l'échelle internationale sur l'éducation, la science, la culture et la communication. En tant qu'agence statistique officielle de l'UNESCO, l'ISU produit un large éventail de bases de données de pointe pour alimenter les politiques et les investissements nécessaires pour transformer des vies et propulser le monde vers ses objectifs de développement. L'ISU offre un accès gratuit aux données pour tous les pays et groupements régionaux de l'UNESCO de 1970 à la dernière année disponible. L'ISU encourage les développeurs et les chercheurs à créer des sites Web et des applications qui exploitent à fond les données de diffusion de l'ISU. En plus d'une puissante API basée sur des normes, l'ISU prend en charge un navigateur de données et un service de téléchargement de données en masse (BDDS).
Keywords: Data collection; Libre accès; ONU; Statistiques

Strategic Corporate Social Responsibility (SCSR): a systematic literature review - Athanasiadou, Chrisalena; Chatzoudes, Dimitrios; Theriou, Georgios (2020 Fourth World Conference on Smart Trends in Systems, Security and Sustainability (WorldS4), 2020)
Over the past few decades, Corporate Social Responsibility (CSR) has been perceived as an antecedent of competitive advantage. It was, moreover, placed at the top of the business agenda and recognized as a key driver of performance. Under this context, the present study sets to investigate how strategic CSR (SCSR) affects organizational performance and whether firms operating in “controversial” sectors should adopt SCSR activities. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. After searching for academic publications in the Scopus database and selecting publications based on their relevance, 32 studies have been included in the review. Their analysis sheds light on common findings and contradicting arguments. Results show the main attributes of strategic, as opposed to non-strategic CSR activities. The importance of effective communication of SCSR activities is highlighted. SCSR is linked to “shared value”, as well as to competitive advantage, social innovation and good reputation. Voices of criticism focus on using SCSR as an empty promise that is used to counteract unethical behavior. Finally, more research is needed on the implementation of SCSR activities during recessionary periods.
Keywords: Co-création; Data collection; Innovation; Libre accès; Méthodes; Recherche; Relations industrielles

Strategic Corporate Social Responsibility (SCSR): a systematic literature review - Athanasiadou, Chrisalena; Chatzoudes, Dimitrios; Theriou, Georgios (2020 Fourth World Conference on Smart Trends in Systems, Security and Sustainability (WorldS4), 2020)
Over the past few decades, Corporate Social Responsibility (CSR) has been perceived as an antecedent of competitive advantage. It was, moreover, placed at the top of the business agenda and recognized as a key driver of performance. Under this context, the present study sets to investigate how strategic CSR (SCSR) affects organizational performance and whether firms operating in “controversial” sectors should adopt SCSR activities. To this aim, this study reviews the body of knowledge on the topic, through a systematic review of the literature. After searching for academic publications in the Scopus database and selecting publications based on their relevance, 32 studies have been included in the review. Their analysis sheds light on common findings and contradicting arguments. Results show the main attributes of strategic, as opposed to non-strategic CSR activities. The importance of effective communication of SCSR activities is highlighted. SCSR is linked to “shared value”, as well as to competitive advantage, social innovation and good reputation. Voices of criticism focus on using SCSR as an empty promise that is used to counteract unethical behavior. Finally, more research is needed on the implementation of SCSR activities during recessionary periods.
Keywords: Co-création; Data collection; Innovation; Libre accès; Méthodes; Recherche; Relations industrielles

Statistiques UIS - UNESCO
L'Institut de statistique de l'UNESCO (ISU) est la source officielle et fiable de données comparables à l'échelle internationale sur l'éducation, la science, la culture et la communication. En tant qu'agence statistique officielle de l'UNESCO, l'ISU produit un large éventail de bases de données de pointe pour alimenter les politiques et les investissements nécessaires pour transformer des vies et propulser le monde vers ses objectifs de développement. L'ISU offre un accès gratuit aux données pour tous les pays et groupements régionaux de l'UNESCO de 1970 à la dernière année disponible. L'ISU encourage les développeurs et les chercheurs à créer des sites Web et des applications qui exploitent à fond les données de diffusion de l'ISU. En plus d'une puissante API basée sur des normes, l'ISU prend en charge un navigateur de données et un service de téléchargement de données en masse (BDDS).
Keywords: Data collection; Libre accès; ONU; Statistiques